Rapid eco-friendly synthesis, characterization, and cytotoxic study of trimetallic stable nanomedicine: A potential material for biomedical applications - Chaturvedi V.K.; Rai S.N.; Tabassum N.; Yadav N.; Singh V.; Bohara R.A.; Singh M.P. (My University, 2025)
In the current scenario of the fight against cancer Integration of potential elements seems to be the best alternative since it overcomes the weaknesses of individuals and the combination of elements makes them formidable in the fight against the cancer war. Inspired by this objective and trusting our knowledge of paddy straw grown oyster mushroom, Pleurotus florida (Pf) mediated synthesis; a first-of-kind approach has been developed for the rapid synthesis of Au–Pt–Ag trimetallic nanoparticles (TMNPs). The developed method was successful, which was confirmed by Ultraviolet–Visible, X-ray diffraction, Transmission Electron Microscopy, Energy Dispersive Spectroscopy. Specifically, prepared TMNPs have been studied for their stability and size as a primary prerequisite for nanomedicine. Finally, the stable nanomedicine developed has been assessed for its performance against the highly metastatic breast cancer cell line (mda-mb-231). The performance was assessed using MTT assay and morphological readings, which were integrated with the cell viability data. We also determined the IC50 value, which was far superior to individual components and motivated us to postulate the possible breast cancer cell killing mechanism of TMNPs. The present study unlocks the new paths for the mushroom-mediated environmentally friendly, economic synthesis of trimetallic nanoparticles, which can be effectively used in cancer nanomedicine. © 2020 The Authors